Effect of free distribution of medicines on the process of care for adult patients with type 1 and type 2 diabetes and hypertension: post hoc analysis of randomised controlled trial findings - Braden Manns; Baiju R Shah; Nav Persaud; Onella Charles; Hannah Woods; Muhamad Ally; Ri Wang (BMJ Open)
Objectives The Carefully Selected and Easily Accessible at No charge Medicines randomised controlled trial showed that patients receiving free access to medicines had improved diabetes and hypertension outcomes compared with patients who had usual access to medicines. In this study, we aimed to test the impact of providing free access to medicine to people with diabetes and hypertension on process of care indicators.Design In this post hoc analysis of randomised controlled trial findings, we identified process of care indicators for the management of diabetes and hypertension using relevant guidelines. The following process of care indicators were identified for diabetes management: encounters with healthcare professionals, blood pressure measurements, self-monitoring of blood glucose, annual eye and foot examination, annual administration of the influenza vaccine, and laboratory testing for glycated haemoglobin (HbA1c), low-density lipoprotein-cholesterol, serum creatinine and urine albumin to creatinine ratio. We identified the following process of care indicators for hypertension: encounters with healthcare professionals, blood pressure measurements, self-measuring of blood pressure, and serum tests for electrolytes, HbA1c, lipids and creatinine. Chart extractions were performed for all patients and the indicators for diabetes and hypertension were recorded. We compared the indicators for patients in each arm of the trial.Results The study included 268 primary care patients. Free distribution of medicines may improve self-monitoring behaviours (adjusted rate ratio (aRR) 1.30; 95% CI 0.66 to 2.57) and reduce missed primary care appointments for patients with diabetes (aRR 0.80; 95% CI 0.48 to 1.33) or hypertension (aRR 0.41; 95% CI 0.18 to 0.90). Free distribution may also reduce primary care and consultant appointments and laboratory testing in patients with hypertension.Conclusions Improving medicine accessibility for patients with diabetes and hypertension not only improves surrogate health outcomes but also improves the patient experience and may also reduce healthcare costs by encouraging self-monitoring.Trial registration number The randomised controlled trial mentioned is clinicaltrials.gov identifier: NCT02744963.